Comparison of methicillin-resistant and methicillin-sensitive Staphylococcus aureus strains isolated from a tertiary hospital in Terengganu, Malaysia - Lim, King Ting; Yeo, Chew Chieng; Suhaili, Zarizal; Thong, Kwai Lin (Institute of Infectious Diseases, 2012)
Staphylococcus aureus is a persistent human pathogen responsible for a variety of infections ranging from soft-tissue infections to bacteremia. The objective of this study was to determine genetic relatedness between methicillin-resistant S. aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) strains. We isolated 35 MRSA and 21 MSSA strains from sporadic cases at the main tertiary hospital in Terengganu, Malaysia, screening them for the presence of virulence genes. Their genetic relatedness was determined by accessory gene regulator (agr) types, PCR-restriction fragment length polymorphism (RFLP) of the coa gene, pulsed-field gel electrophoresis (PFGE), S. aureus protein A (spa), and multilocus-sequence typing (MLST). We found that 57% of MRSA and 43% of MSSA strains harbored enterotoxin genes. The majority (87.5%) of the strains were agr type I. PCR-RFLP and PFGE genotyping of the coa gene revealed that MRSA strains were genetically related, whereas MSSA strains had higher heterogeneity. The combined genotype, MLST-spa type ST239-t037, was shared among MRSA and MSSA strains, indicating that MRSA strains could have evolved from MSSA strains. Two combined MLST-spa types were present in MRSA strains, whereas 7 different MLST-spa types were detected in MSSA strains, including 2 combined types (ST779-t878 and ST1179-t267) that have not been reported in Malaysia. In conclusion, enterotoxin genes were more prevalent in MRSA than in MSSA strains in the Terengganu hospital. The MSSA strains were genetically more diverse than the MRSA strains.